Solar drying of peppermint leave: Thermal characteristics, drying kinetics, and quality assessment. (January 2023) - Kant, Ravi; Kushwah, Anand; Kumar, Anil; Kumar, Mahesh
Abstract: In the present study, thermal performance of greenhouse solar dryer (GHSD) was analyzed at full load of peppermint leaves for dehydration. The experiments were conducted in both GHSD and sun drying processes to compare drying characteristics, thermal properties, and quality assessment of peppermint leaves. The maximum drying cabin temperature attained during the experimentation was 58.3 °C at solar radiation 864W/m 2 . Initial moisture content of peppermint leaves 81.25% reduced to 11.22% and 22% within 10 h in GHSD and sun drying, respectively. Drying rate was obtained as 0.65 kg water/kg solid.hr and 0.61 kg water/kg solid.hr for GHSD and sun drying process at the end of the experiment. Verma et al. model accurately defined the drying characteristics of peppermint leaves in GHSD and sun drying. Average effective moisture diffusivity ( D e f f ), mass transfer coefficient ( h m ) and heat transfer coefficient ( h ) of peppermint leaves were increased by 12.76%, 17.71%, and 64.23%, correspondingly in GHSD compared to sun drying. Activation energy ( E a ) of peppermint leaves was computed as 32.25 kJ/mol in GHSD, while in sun drying method, it was 59.68 kJ/mol. Water activity ( A w ) peppermint leaves were 0.850, 0.705, 0.385 and 0.850, 0.765, 0.520 at 8, 14, 19 h in GHSD and sun drying. Graphical abstract: Image 1 Highlights: Greenhouse solar dryer (GHSD) was designed and fabricated for peppermint leaves. Thermal characteristics, drying kinetics, and quality assessment of peppermint leaves were evaluated in GHSD and sun drying. Verma et al. model was best fit drying model to explain drying behaviour of peppermint leaves in GHSD and sun drying. Activation energy ( E a ) of peppermint leaves was computed as 32.25 kJ/mol and59.68kJ/mol in GHSD and sun drying respectively.